2020
DOI: 10.5588/ijtld.19.0224
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of guidelines for the management of Mycobacterium tuberculosis infection in children

Abstract: OBJECTIVE: The quality of paediatric clinical practice guidelines (CPGs) for the management of Mycobacterium tuberculosis infection is unclear. We aimed to comprehensively assess the quality of these CPGs and identify areas requiring improvement.DESIGN: CPGs were systematically searched and identified before being appraised by independent reviewers using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) and Reporting Items for Practice Guidelines in HealThcare (RIGHT) tools. Inter-rater re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…We also found that the specific approaches or methods used to elicit or identify value and preferences or resource implications were poorly reported. Similar findings were also observed in other guideline evaluations regarding other topics (21,48). Generally, the methodological quality relies on documented information, and reporting quality can to some extent also mirror the methodological quality (49).…”
Section: Discussionsupporting
confidence: 86%
“…We also found that the specific approaches or methods used to elicit or identify value and preferences or resource implications were poorly reported. Similar findings were also observed in other guideline evaluations regarding other topics (21,48). Generally, the methodological quality relies on documented information, and reporting quality can to some extent also mirror the methodological quality (49).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the highquality CPGs should always provide relative information on the appropriateness of recommendations in any clinical situation (39). Furthermore, it is notable that the values and preferences of the target population, as well as the cost and resource implications in the formulation of each recommendation (item 14a/b) were poorly reported, which was consistent with the results in the guideline evaluation regarding other topics (40,41).…”
Section: Discussionmentioning
confidence: 73%